Building blocks of academic writing - Brooks, Carellin; Bruno, Crystle M.; Coelho, Fabio; Gambrill, Peter; Hagemann, Jen; Jebens, Jen; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2020)
"Building Blocks of Academic Writing covers typical writing situations for developing academic writers, from prewriting and research through expressing themselves online. Developmental work in different types of paragraphs--descriptive, narrative, expository, persuasive--allows students to build capacity for longer essays. Each chapter includes review questions with a Canadian focus that instructors can assign to help students practise the skills developed in the text. This book aligns with the BC ABE Level: Intermediate English"--BC Campus website.
This work is licensed under the Creative Commons Attribution International CC-BY-NC.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on June 24, 2020).
Keywords: Academic writing -- Textbooks; Electronic books